Transformational leadership: a style of motivating employees - Susilo, Donny (MEC-J (Management and Economics Journal), 2018)
The common problem faced by company today is related to human resource management and development especially in career advance. Many of unsatisfied employees make company difficult to achieve target. Motivation can be enhanced by a kind of leadership that devotes its attention to the problems faced by its followers and the development needs of each of its followers by encouraging and encouraging them to achieve the goals. Transformational leadership has 4 functions in motivating employees, namely the dimensions of charisma, inspiration motivation, intellectual stimulation, attention to the individual. By the implementation of transformational leadership, the psychological aspects of employees can be mastered so that leads to increased motivation. Transformational leadership is good to apply in both government institution and private company.